INSTALLATION FOR MEASURING STRESS RELAXATION IN POLYMER MATERIALS UNDER FRICTION AND WEAR CONDITIONS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The work assessed the need to predict the relaxation properties of polymers, which is important for ensuring the durability of parts of mechanical engineering structures made of polymer materials. The factors influencing the performance of products made of polymer materials, as well as the need to determine and predict the durability of parts operating under friction conditions at a constant amount of deformation, have been studied.To determine by experimental method the stress relaxation indicators of polymer materials under conditions of friction and wear, a device has been developed - a triborelaxometer. A description of the installation design, loading and loading conditions, as well as the coefficient of friction in the polymer-counterbody pair is given.